Relevansi Penentuan Kuantitas Mahar dalam Pernikahan Masyarakat Bugis di Kecamatan Mendahara Perspektif Maslahah dan Urf - Ilham, Amar Muhammad; Umar, Hasbi; Ramlah, Ramlah; Arsyad, Arsyad (Prodi Hukum Ekonomi Syariah (Muamalah), 2023)
This research is the relevance of determining the quantity of dowry in Bugis weddings in the Mendahara sub-district from the perspective of Maslahah and Urf. The purpose of this study is first, to provide the results of a study of how the quantity of dowry is in the Bugis community in Mendahara District. Second, to examine how the relevance of dowry is to the social strata of the Bugis community in Mendahara District. Third, to analyze how Islamic law relates to the phenomenon of the quantity of dowry in the Bugis community in Mendahara District. This method is used to research on natural object conditions where the researcher is the key instrument. The results of this study indicate that the Bugis community in Mendahara District and in several other Bugis areas cannot differentiate the values ​​between dui' menre and sompa. This may be due to the hedonistic modern social lifestyle, where people only see lively weddings in the area.